Ornamental Palms for South Florida - Robert Black; Timothy K. Broschat (EDIS)
Typically, palms will fare better in windstorms than broadleaf trees, but some are even better adapted than others. Proper palm selection will improve the chances of a palm thriving in a particular location. This document lists a number of species that can be grown in south Florida landscapes. Although many other species have been successfully grown in south Florida, they are relatively rare in the nursery industry and thus are not readily available. First published in May 1988.